An ultra-wideband printed dipole antenna of the frequency range from 1 to 3 GHz with wide-angle scanning in the E-plane and low level of cross polarization. (March 2020) - Gevorkyan, A V
Abstract: The paper presents the design of the developed ultra-wideband printed dipole antenna. The frequency characteristics of the antennas for different values of the scanning angle in the E-plane are given. When scanning in the angle sector ±50° the operating frequency band of the antenna is in the frequency range from 1 to 3 GHz at the level of the VSWR less than 3. The realized gain is up to 1.5 dB and the antenna efficiency is more than 77%. The cross polarization of the realized gain at all values of the scanning angle is less than minus 27.5 dB.